Accessing AutoCAD Architecture 2008 - William Wyatt (Thomson Delmar Learning, 2008)
Written for all levels of expertise, William Wyatt's widely used Accessing AutoCAD Architecture offers engaging step-by-step tutorials and projects that clearly demonstrate and reinforce the real-world application of AutoCAD Architecture tools. Wyatt introduces each tool and then provides a thorough explanation of the options of the command and how it is used in the development of drawings. Users gain familiarity with AutoCAD Architecture through the use of applications that involve the creation of floor plans, foundation plans, elevations, sections, details, and presentation drawings for a two-story residence, including a basement. Additional tutorials survey techniques for creating architectural and structural drawings for commercial buildings. The book examines the use of the Detail Component Manager and the keynoting of details as well as the newest features of annotation and the Project Navigator for creating working drawings as a project progresses